2000
DOI: 10.1002/1098-0997(2000)8:5<248::aid-idog1028>3.3.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of diagnostic tests for vaginal trichomoniasis

Abstract: Objective: To review critically and to summarize the evidence of diagnostic tests and culture media for the diagnosis of Trichomonas vaginitis.Methods: We performed a systematic review of literature indexed in MEDLINE of studies that used Trichomonas culture as the reference standard (9,882 patients, 35 studies). Level I studies (5,047 patients, 13 studies) fulfilled at least two of three criteria: 1) consecutive patients were evaluated prospectively, 2) decision to culture was not influenced by test results, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 2 publications
(2 reference statements)
0
15
0
4
Order By: Relevance
“…Five studies which dealt with the performance of ELISAs have been reviewed; their pooled sensitivity was 82% and pooled specificity was 73% [10]. The ELISA using mixed lysate Ag in the present study demonstrated higher specificity (100%) than the pooled data, while their sensitivity was similar to that of the pooled data.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 52%
“…Five studies which dealt with the performance of ELISAs have been reviewed; their pooled sensitivity was 82% and pooled specificity was 73% [10]. The ELISA using mixed lysate Ag in the present study demonstrated higher specificity (100%) than the pooled data, while their sensitivity was similar to that of the pooled data.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 52%
“…Trichomonas, the most common non-viral sexually transmitted disease, with approximately 170 million newly acquired infections of T. vaginalis worldwide annually, has been linked to sterility, pre-term delivery, low birth weight and high infant mortality and, more recently, to increased susceptibility to HIV infection (Petrin et al 1998;Patel et al 2000;Upcroft and Upcroft 2001;Schwebke and Burgess 2004;Cudmore et al 2004;Dunne et al 2003). It is responsible for 11% of all cases of non-gonoccocal urethritis as well as prostatitis, epididymitis and infertility in males (Petrin et al 1998;Cudmore et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…8 The conventional Papanicolaou (Pap) smear (CPS) has been shown to be ineffective in diagnosing T. vaginalis in asymptomatic women, lacking both sensitivity and specificity. 9,10 A recent meta-analysis reported a pooled sensitivity of 57% and a specificity of 97% for the diagnosis of T. vaginalis in CPS when compared with culture as a gold standard. 10 A number of older studies even stressed the lack of specificity of CPS, finding them to have more than 30% false positive results.…”
mentioning
confidence: 99%